THE SITUATION OF CONTRACTS IN THE FACE OF THE COVID-19 PANDEMIC (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The changes resulting from the pandemic resulted in a process of intense changes in the entire Brazilian legal body. As the pandemic is of a global nature, it has given rise to intense administrative and legislative transformations for national and global state standards. Thus, it is necessary to study and delimit the problem from the theoretical point of view, aiming at an adequate solution to the issue. In this perspective, the work was based on the changes that occurred in the contractual law, arising from the period of public calamity, these being implemented in the federal, state and municipal spheres. In particular, the investigation aimed to identify and analyze the proposals and measures established in the national territory, mainly in civil, consumer, administrative, business and real estate contracts, addressing their most relevant changes, within the Brazilian legal paradigm.